Preparation method of quaternary ammonium salt cation surface modified calcium carbonate for papermaking
By coupling silane coupling agent on the surface of calcium carbonate and introducing quaternary ammonium monomers, the charge properties are changed, and the problem of calcium carbonate being difficult to fusion with fibers in papermaking is solved, and the mechanical strength and fiber retention of the paper are improved. It reduces the difficulty of treating white water and reduces the use of cationic additives, achieving a green and economical papermaking effect.
Patent Information
- Application Number
- CN202411234816.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, calcium carbonate is difficult to fuse with paper fibers due to high negative charge and high hydrophilicity during papermaking, which increases the cost of water filtration and reduces the quality of paper, and the cationic additives used are harmful to the environment.
By coupling silane coupling agent on the surface of light calcium carbonate and introducing quaternary ammonium monomers, the charge properties of the surface are changed, negative charge and hydrophilicity are reduced, and calcium carbonate is formed on the surface modified surface of the quaternary ammonium carbonate, which improves its Binding power with fibers.
It significantly improves the mechanical strength and fiber retention rate of paper, reduces the difficulty of white water treatment, and reduces the use of cationic additives, which has the advantage of green economy.
Smart Images

Figure CN119119773A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymers and composite materials, and in particular to a method for preparing calcium carbonate with surface modified by quaternary ammonium salt cations for papermaking. Background Art
[0002] Calcium carbonate is one of the most widely used inorganic mineral powder raw materials in the papermaking industry. As a commonly used filler and coating agent in the papermaking process, calcium carbonate can improve paper quality, increase paper opacity, and improve production efficiency. However, the surface of calcium carbonate contains a large number of hydroxyl groups and has a significant negative charge, and the surface of paper fibers has a large number of carboxyl groups and is also negatively charged. Therefore, calcium carbonate and paper fibers are actually mutually repelled and difficult to fuse. In addition, the high hydrophilicity of calcium carbonate itself makes it easier to filter out with water during filtration, which not only increases the cost of filtration treatment, but also reduces the paper properties of the filter cake. Reducing the negative charge on the surface of calcium carbonate and reducing its surface hydrophilicity is of great significance to improving its application effect in the field of papermaking. Modification can effectively improve the binding force between calcium carbonate and paper fibers, reduce the cost of filtration treatment, and increase the retention rate of pulp on the mesh. A high retention rate means that the fibers are effectively retained on the mesh, thereby improving the mechanical strength of the paper. At the same time, a high retention rate means that the concentration of white water under the mesh is reduced, thereby reducing the difficulty of white water recovery and improving the economic effect of calcium carbonate application in papermaking.
[0003] At present, unmodified light calcium carbonate is widely used in papermaking industry. Light calcium carbonate is abundant in source and cheap in price. It has small particles and high whiteness, which can significantly improve the brightness of paper, increase the ink absorption of paper, and make paper tight. However, unmodified calcium carbonate itself has a high negative charge, which aggravates the aggregation of paper materials, thereby increasing the amount of cationic additive polyacrylamide. Polyacrylamide decomposes slowly and easily accumulates in the environment, which may cause water pollution and soil quality degradation. In addition, polyacrylamide has a certain impact on human health. Long-term or excessive intake will cause certain damage to the skin, respiratory tract, nervous system, etc. Therefore, modifying the light calcium carbonate raw material to weaken its original strong negative charge can reduce the amount of cationic additives, which is of great significance for green production and economic benefits.
[0004] At present, calcium carbonate has been modified with cationic starch to form starch-coated calcium carbonate, which increases the binding force between fiber and filler. However, the starch layer has high solubility, and the dissolved starch will disturb the ion balance in the entire papermaking system, thereby causing flocculation of the slurry, further leading to a decrease in paper uniformity, and accumulating in white water to produce resin, rotten pulp and adhesion, thereby increasing the cost of white water recovery and processing. Based on this, the present invention uses quaternary ammonium salts to modify light calcium carbonate to obtain light calcium carbonate with low surface hydrophilicity and low negative charge, which is used as a papermaking synergist to achieve the excellent effect of improving the mesh retention rate of pulp and improving economic benefits, and helping the development of green economy in my country's papermaking industry. Summary of the invention
[0005] Therefore, in order to overcome the above-mentioned shortcomings, the present invention provides a method for preparing calcium carbonate with quaternary ammonium salt cation surface modification for papermaking, wherein the surface of light calcium carbonate is rich in a large amount of hydroxyl groups, a silane coupling agent is first connected to the surface through a coupling reaction, thereby introducing a C=C bond, and then a quaternary ammonium salt monomer is accessed to the surface through an addition polymerization reaction, and finally a cationic group is connected to change the charge property of the calcium carbonate surface. The modification method is simple and has excellent effect. The bonding force of calcium carbonate and fiber can be effectively improved, the retention rate of fiber and filler in the papermaking process can be improved, the mechanical strength of paper can be improved, and the fiber and filler content in white water can be reduced simultaneously, thereby reducing the difficulty of papermaking white water treatment.
[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing calcium carbonate surface-modified with quaternary ammonium salt cations for papermaking, comprising the following steps:
[0007] (1) placing 5-30 parts by weight of unsurface-modified calcium carbonate powder and 100-250 parts by weight of an alcohol-water mixed solution in a reaction vessel, adding a certain amount of a silane coupling agent and stirring evenly, heating the mixed reaction system to 80±5° C. and stirring for 6-8 hours; after the reaction is completed, centrifugally separating the calcium carbonate, drying, and grinding;
[0008] (2) Disperse 5-30 parts by weight of the modified calcium carbonate powder in step (1) in 100-300 parts by weight of deionized water, then add 8-20 parts by weight of quaternary ammonium salt cationic monomer, stir evenly, heat in a water bath to 60-65° C. under nitrogen protection, add 0.08-0.2 parts by weight of an initiator dispersed in 10-20 parts by weight of water to initiate polymerization in the reaction system, maintain the water bath temperature and stir the reaction for 5-10 hours. After the reaction is completed, centrifuge and wash, and dry at 80-110° C. to obtain calcium carbonate powder with quaternary ammonium salt cationic surface modification.
[0009] Preferably, the mass ratio of ethanol to water in the ethanol-water mixed solution is 0-9:1;
[0010] Preferably, the silane coupling agent is a siloxane containing a carbon-carbon double bond, including one or more of vinylmethyldiethoxysilane, vinyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0011] Preferably, the quaternary ammonium salt monomer modifier is a quaternary ammonium salt monomer containing a carbon-carbon double bond, including one or more of methacryloyloxyethyl trimethyl ammonium chloride (DMC), acryloyloxyethyl trimethyl ammonium chloride (DAC), methyl diallyl ammonium chloride (DMDAAC), methacrylamidopropyl trimethyl ammonium chloride (MAPTAC), and acrylamidopropyl trimethyl ammonium chloride (APTAC);
[0012] Preferably, the mass ratio of the silane coupling agent to calcium carbonate is 1-2:1.
[0013] Preferably, the initiator is one of ammonium persulfate and potassium persulfate.
[0014] The present invention has the following advantages: (1) The present invention connects positively charged groups on the surface of light calcium carbonate, which generates charge attraction between the positively charged groups on the surface of the fiber, so that the light calcium carbonate and the fiber can be better combined, and the retention rate of paper fiber in papermaking application is significantly improved. It can be promoted and applied as a modified calcium carbonate powder material for papermaking.
[0015] (2) The present invention introduces a quaternary ammonium group having a bacteriostatic and sterilizing function into calcium carbonate powder, which can provide anti-mildew properties to paper products when used in the papermaking industry.
[0016] (3) The method of the present invention is simple, has low production cost, high production efficiency, and is easy to be mass-produced industrially. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The infrared spectrum of the calcium carbonate powder prepared under the two reaction conditions of steps (1) and (2) in Example 1;
[0018] Figure 2 The contact angle test diagram of the first and second step modified materials in Example 1;
[0019] Figure 3 This is a schematic diagram of the preparation reaction of calcium carbonate surface modified by quaternary ammonium salt cations. DETAILED DESCRIPTION
[0020] The following will be combined with the attached Figure 1-Figure 3The present invention is described in detail, and the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The present invention provides a method for preparing calcium carbonate surface-modified with quaternary ammonium salt cations for papermaking, which is specifically implemented as follows;
[0022] Embodiment 1:
[0023] A method for preparing calcium carbonate surface-modified with quaternary ammonium salt cations for papermaking comprises the following steps:
[0024] (1) Place 8g of unsurface-modified calcium carbonate powder and 220g of ethanol-water mixed solution in a reaction container, add 8g of silane coupling agent KH-570 (γ-methacryloxypropyltrimethoxysilane) and stir evenly, heat the mixed reaction system to 80°C and stir for 6h; after the reaction, centrifuge to separate the calcium carbonate, wash it twice with anhydrous ethanol, and then wash it twice with deionized water. Finally, vacuum dry the powder at 80°C for 24h. Grind and crush it for later use;
[0025] (2) 8 g of the modified calcium carbonate powder in step (1) was dispersed in 300 g of deionized water, and then 8.105 g of DAC (acryloyloxyethyl trimethyl ammonium chloride, BASF) monomer was added, stirred evenly, heated to 60° C. in a water bath under nitrogen protection, and a solution of 0.162 g of initiator ammonium persulfate dispersed in 10 g of water was added to the reaction system to initiate polymerization, and the water bath temperature was maintained and stirred for 6 h. After the reaction was completed, the mixture was centrifuged and washed, and dried at 80° C. to obtain calcium carbonate powder with quaternary ammonium salt cation surface modification.
[0026] Embodiment 2:
[0027] A method for preparing calcium carbonate surface-modified with quaternary ammonium salt cations for papermaking comprises the following steps:
[0028] (1) 10 g of unsurface-modified calcium carbonate powder and 250 g of ethanol-water mixed solution are placed in a reaction container, 10 g of silane coupling agent KH-570 (γ-methacryloxypropyltrimethoxysilane) is added and stirred evenly, the mixed reaction system is heated to 80° C. and stirred for 8 h; after the reaction is completed, the calcium carbonate is centrifuged and separated, dried, ground and pulverized for later use;
[0029] (2) Disperse 5 g of the modified calcium carbonate powder in step (1) in 150 g of deionized water, then add 8 g of DAC (acryloyloxyethyl trimethyl ammonium chloride, BASF) monomer, stir evenly, heat to 60° C. in a water bath under nitrogen protection, add 0.08 g of initiator ammonium persulfate dispersed in 10 g of water to the reaction system to initiate polymerization, maintain the water bath temperature and stir for 6 h. After the reaction is completed, centrifuge and dry at 80° C. to obtain calcium carbonate powder with quaternary ammonium salt cation surface modification.
[0030] Embodiment 3:
[0031] A method for preparing calcium carbonate surface-modified with quaternary ammonium salt cations for papermaking comprises the following steps:
[0032] (1) 5 g of unsurface-modified calcium carbonate powder and 180 g of ethanol-water mixed solution are placed in a reaction container, 5 g of silane coupling agent KH-570 (γ-methacryloxypropyltrimethoxysilane) is added and stirred evenly, the mixed reaction system is heated to 80° C. and stirred for 8 h; after the reaction is completed, the calcium carbonate is centrifuged and separated, dried, ground and pulverized for later use;
[0033] (2) 30 g of the modified calcium carbonate powder in step (1) was dispersed in 150 g of deionized water, and then 10 g of DAC (acryloyloxyethyl trimethyl ammonium chloride, BASF) monomer was added, stirred evenly, heated to 60° C. in a water bath under nitrogen protection, and a solution of 0.2 g of initiator ammonium persulfate dispersed in 10 g of water was added to the reaction system to initiate polymerization, and the water bath temperature was maintained and stirred for 6 h. After the reaction was completed, the mixture was centrifuged and dried at 80° C. to obtain calcium carbonate powder with quaternary ammonium salt cation surface modification.
[0034] Figure 1 This is the infrared spectrum of the calcium carbonate powder prepared under the two reaction conditions of steps (1) and (2) in Example 1. As shown in the figure, the first step modified material has more characteristic peaks of 1720cm-1 and 1640cm-1 than before modification, which represent C=O bond and C=C bond respectively, indicating that KH570 has been successfully connected to the surface of light calcium carbonate, proving that the first step modification of the material is successful. In addition, the second step modified material has less C=C bond characteristic peaks than the first step modified material, indicating that C=C and DAC have undergone polymerization reaction, proving that the second step modification of the material is successful.
[0035] Figure 2The contact angle test diagram of the first and second step modified materials in Example 1. It can be seen from the figure that the contact angle of the light calcium carbonate before modification is 15°, and the contact angle of the light calcium carbonate after the first step modification is 40°. The hydrophobic groups in the surface KH-570 are successfully connected to the surface of the light calcium carbonate, proving that the first step modification of the material is successful. In addition, the contact angle of the light calcium carbonate after the second step modification is 25°, which is smaller than the contact angle of the light calcium carbonate after the first step modification. The hydrophilic groups in the surface DAC are successfully connected to the surface of the material, proving that the second step modification of the material is successful.
[0036] Table 1 shows the experimental results of pulp retention rate of the modified light calcium carbonate prepared in Example 1 as a papermaking filler. In the experiment, bleached eucalyptus hardwood pulp and bleached coniferous wood pulp were first put into a crusher at a mass ratio of 4:1, and 200 ml of deionized water was added. A comparative experiment was conducted in the crusher without adding light calcium carbonate, adding unmodified light calcium carbonate, and adding the modified light calcium carbonate prepared in Example 1. The light calcium carbonate was evenly dispersed and crushed in water for more than 3 minutes, and the solution was poured into an 80-mesh sieve and rinsed with deionized water 3 times. The sieve was placed in a blast drying oven and dried at 105±5°C for 24 hours. Among them, the mass of the sieve after filtration minus the mass of the sieve before filtration is the lost mass. Among them:
[0037] Overall retention rate = (mass added - mass lost) / mass added
[0038] The calculated results are shown in Table 1:
[0039]
[0040]
[0041] From the overall retention rates of experiments (1), (2), (3) and experiments (4), (5) and (6), it can be seen that the modified light calcium carbonate in Example 1 can significantly improve the fiber retention rate, proving that it has excellent properties as a papermaking filler.
[0042] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing calcium carbonate surface-modified with quaternary ammonium salt cations for papermaking, characterized in that: The following steps are involved: (1) placing 5-30 parts by weight of unsurface-modified calcium carbonate powder and 100-250 parts by weight of an ethanol-water mixed solution in a reaction vessel, adding a certain amount of a silane coupling agent and stirring evenly, heating the mixed reaction system to 80±5° C. and stirring for 6-8 hours; after the reaction is completed, centrifugally separating the calcium carbonate, drying, and grinding; (2) dispersing 5-30 parts by weight of the modified calcium carbonate powder obtained in step (1) in 100-300 parts by weight of deionized water, then adding 8-20 parts by weight of a quaternary ammonium salt cationic monomer, stirring evenly, passing nitrogen through the reaction system for 30 minutes, further heating the reaction system to 60-65° C. under nitrogen protection, adding 0.08-0.2 parts by weight of an initiator dissolved in 10-20 parts by weight of water to the reaction system, initiating a polymerization reaction, maintaining the temperature of the reaction system at 60-65° C. and stirring the reaction for 5-10 hours; after the reaction is completed, centrifuging and drying at 80-110° C. to obtain calcium carbonate powder with a surface modified with a quaternary ammonium salt cationic monomer.
2. A method for preparing calcium carbonate surface-modified by quaternary ammonium salt cations for papermaking according to claim 1, characterized in that: The mass ratio of ethanol to water in the ethanol-water mixed solution is 0-9:
1.
3. A method for preparing calcium carbonate surface-modified by quaternary ammonium salt cations for papermaking according to claim 1, characterized in that: The silane coupling agent is a siloxane containing a carbon-carbon double bond, including one or more of vinylmethyldiethoxysilane, vinyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
4. A method for preparing calcium carbonate surface-modified by quaternary ammonium salt cations for papermaking according to claim 1, characterized in that: The quaternary ammonium salt monomer modifier is a quaternary ammonium salt monomer containing a carbon-carbon double bond, including one or more of methacryloyloxyethyl trimethyl ammonium chloride (DMC), acryloyloxyethyl trimethyl ammonium chloride (DAC), methyl diallyl ammonium chloride (DMDAAC), methacrylamidopropyl trimethyl ammonium chloride (MAPTAC), and acrylamidopropyl trimethyl ammonium chloride (APTAC).
5. A method for preparing calcium carbonate surface-modified by quaternary ammonium salt cations for papermaking according to claim 1, characterized in that: The mass ratio of the silane coupling agent to calcium carbonate is 1-2:
1.
6. A method for preparing calcium carbonate surface-modified by quaternary ammonium salt cations for papermaking according to claim 1, characterized in that: The initiator is one of ammonium persulfate and potassium persulfate.
